Comparison of Horizontal Corneal Diameter Measurements Using Orbscan IIz, OPD Scan III, and IOLMaster 700. Issue 10 (October 2021) - Cruz, Sebastian; Valenzuela, Felipe; Stoppel, Juan; Maul, Eugenio; Gibbons, Allister
Abstract : Purpose: To compare three automated devices for measuring the horizontal corneal diameter (white to white [WTW]). Methods: In 65 eyes of 38 patients, the WTW distance was measured independently by three examiners using the following techniques: Orbscan IIz tomography system (Bausch & Lomb), IOLMaster 700 (Carl Zeiss Meditec), and OPD Scan III (NIDEK). We tested for systematic differences in measurements and estimated the limits of agreement (LoA) using linear mixed-effects models. Results: The mean WTW distance was 11.8±0.40 mm with Orbscan IIz, 12.1±0.5 mm with IOLMaster 700 and 12.0±0.4 mm with OPD Scan III. The mean difference between IOLMaster 700 and Orbscan IIz was 0.33 (95% CI, 0.28 to 0.38; P <0.001), between OPD Scan III and Orbscan IIz was 0.24 mm (95% CI, 0.21 to 0.28; P <0.001), and between IOL Master 700 and OPD Scan III was 0.09 (95% CI, 0.05 to 0.12; P <0.001). The 95% LoA for Orbscan IIz versus IOLMaster 700 was −0.69 to 0.03 mm, Orbscan IIz versus OPD Scan III was −0.52 to −0.03 mm, and OPD versus IOLMaster 700 was −0.39 to 0.22 mm. Conclusions: The data suggest that these devices are not interchangeable for usual clinical practice. Adjustments based on mean differences were not enough to compensate for interinstrument discrepancy in WTW measurements.